2007
DOI: 10.1200/jco.2006.08.8054
|View full text |Cite
|
Sign up to set email alerts
|

Improved Overall Survival in Postmenopausal Women With Early Breast Cancer After Anastrozole Initiated After Treatment With Tamoxifen Compared With Continued Tamoxifen: The ARNO 95 Study

Abstract: Postmenopausal women who have taken tamoxifen for 2 years as adjuvant therapy are less likely to experience a recurrence of breast cancer and have improved overall survival if they switch to anastrozole compared with continuing to receive tamoxifen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
142
0
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(151 citation statements)
references
References 13 publications
2
142
0
7
Order By: Relevance
“…However, for convenience, the detection of CTCs could be used as an alternative to bone marrow for the identification of occult breast cancer cells and for monitoring minimal residual disease. This is of particular interest in the light of the results of recent trials, indicating that sequential treatment during the disease-free period may improve OS in breast cancer (Coombes et al, 2007;Kaufmann et al, 2007). Conceivably, secondary adjuvant treatment could be administered in patients selected on the basis of persisting CTCs.…”
Section: Discussionmentioning
confidence: 99%
“…However, for convenience, the detection of CTCs could be used as an alternative to bone marrow for the identification of occult breast cancer cells and for monitoring minimal residual disease. This is of particular interest in the light of the results of recent trials, indicating that sequential treatment during the disease-free period may improve OS in breast cancer (Coombes et al, 2007;Kaufmann et al, 2007). Conceivably, secondary adjuvant treatment could be administered in patients selected on the basis of persisting CTCs.…”
Section: Discussionmentioning
confidence: 99%
“…One of the primary unresolved considerations is whether these drugs should be used instead of tamoxifen as initial adjuvant treatment for postmenopausal women with successfully resected EBC, or whether 2-3 years of tamoxifen should precede the implementation of AI therapy. The latter strategy, using either exemestane [Intergroup Exemestane Study (IES)] or anastrozole (Arimidex Nolvadex [ARNO] 95 study and others) as endocrine therapy following 2-3 years of tamoxifen, potentially offers treatment cost savings relative to upfront AIs and significant improvements in DFS, event-free survival (EFS), and overall survival (OS) relative to tamoxifen alone [5][6][7]11]. A significant caveat of the switching approach is that it effectively ''misses'' a sizable number of women who may relapse during the initial treatment period with tamoxifen; these patients have been excluded from AI switching trials such as the IES and ARNO 95 [5,11].…”
Section: Introductionmentioning
confidence: 99%
“…The latter strategy, using either exemestane [Intergroup Exemestane Study (IES)] or anastrozole (Arimidex Nolvadex [ARNO] 95 study and others) as endocrine therapy following 2-3 years of tamoxifen, potentially offers treatment cost savings relative to upfront AIs and significant improvements in DFS, event-free survival (EFS), and overall survival (OS) relative to tamoxifen alone [5][6][7]11]. A significant caveat of the switching approach is that it effectively ''misses'' a sizable number of women who may relapse during the initial treatment period with tamoxifen; these patients have been excluded from AI switching trials such as the IES and ARNO 95 [5,11]. Interestingly, in the Austrian Breast and Colorectal Study Group trial 8, the only reported sequencing trial that randomized patients at the time of surgery, the inclusion of recurrences during the tamoxifen period effectively negated the significant EFS benefit that was observed when these patients were not considered (hazard ratio [HR], 0.63; P = 0.010 compared with HR, 0.76; P = 0.068) [12].…”
Section: Introductionmentioning
confidence: 99%
“…This may reflect the fact that AIs do not display the well-known protective effect of tamoxifen, although no evidence is present of any increase as compared with placebo (Jakesz et al 2005, Kaufmann et al 2007, Forbes et al 2008, Bliss et al 2012, Dubsky et al 2012, Boccardo et al 2013.…”
Section: Cardiovascular Adverse Eventsmentioning
confidence: 94%